2019
DOI: 10.1186/s13643-019-1201-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with poor mental health among healthcare professionals in low- and lower-middle-income countries: a systematic review protocol

Abstract: BackgroundA healthy and productive health workforce is central to a well-functioning health system. However, health workers are at high risk of poor psychological wellbeing due to their particularly strenuous work demands. While mental health of health workers is a well-researched issue in high-income countries, research from low- and lower-middle-income countries (LLMIC) has begun to emerge only recently. The review aims to synthesize this body of research, specifically to assess the prevalence of mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…We performed a systematic search of the literature on mental health and psychological wellbeing of clinical skilled healthcare personnel working in all care settings in low-and lower-middle income countries worldwide, up to the end of 2019. The review had initially been intended as a systematic review and metaanalysis of the available evidence; the protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO) (registration number: CRD42019140036), and has been published [20]. However, following the search and screening steps and as the high number of relevant studies and the methodological issues highlighted in this article became apparent, we concluded that it would be preferable to rede ne our research question also as a precursor to future research and systematic reviews [21,22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a systematic search of the literature on mental health and psychological wellbeing of clinical skilled healthcare personnel working in all care settings in low-and lower-middle income countries worldwide, up to the end of 2019. The review had initially been intended as a systematic review and metaanalysis of the available evidence; the protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO) (registration number: CRD42019140036), and has been published [20]. However, following the search and screening steps and as the high number of relevant studies and the methodological issues highlighted in this article became apparent, we concluded that it would be preferable to rede ne our research question also as a precursor to future research and systematic reviews [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…In regards to the latter, we also included "motivation" and "satisfaction" as search terms, based on our experience that studies labelled as such sometimes contain mental health measures as part of the motivation or satisfaction measurement tool. The search strategy for MEDLINE is provided in the protocol [20]. Search strategies for the other databases were adapted according to their speci c requirements.…”
Section: Information Sources and Search Strategymentioning
confidence: 99%
“…Relating to the study of Dweik, et. al (2016), other researchers including Dzay, et. al (2019), had focused on the factors and prevalence that are associated with poor mental health among healthcare professionals in low-and lower-middle income countries.…”
Section: Incomementioning
confidence: 95%
“…In analyzing the prevalence of mental health care issues among healthcare professionals in lowand lower-middle-income countries and determining the factors that are associated with positive or poor mental health. The review by Dzay, et. al (2019), aims to have a synthesis of all available information for health system managers and policy makers which also highlight the gaps in identifying other possible parameters.…”
Section: Incomementioning
confidence: 99%
“…Our study aims to address this knowledge gap by building on a systematic review of the quantitative literature on mental health and psychological wellbeing of clinical skilled healthcare personnel working in all settings of care in LLMIC worldwide 9,11 . Specifically, the quality issues highlighted by this and prior similar reviews [5][6][7][8] inspired efforts to return to the identified literature to undertake a more detailed quality assessment, with a focus on the measurement of prevalences of mental illness, to generate an in-depth understanding of the methodological strengths and weaknesses and to distil concrete recommendations as to how research could be improved in the future.…”
Section: Introductionmentioning
confidence: 99%